2018
DOI: 10.1108/add-08-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Harm reduction in a Norwegian housing first project: a qualitative study of the treatment providers’ practice

Abstract: Purpose Little is known about how harm reduction is practiced in Norwegian housing first (HF) projects. The purpose of this paper is to explore, describe, and interpret how providers apply a harm reduction approach within a housing project focused on individuals who are homeless with co-morbid substance use and mental health problems. Design/methodology/approach This qualitative study was part of a larger evaluation study of a three-year HF project in a Norwegian municipality. Data were collected using four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
(54 reference statements)
0
12
0
2
Order By: Relevance
“…Similary, both Baxter et al (2019) and Beaudoin (2016) found that HF resulted in no clear differences in substance use when compared with treatment as usual. Qualitative research from a Norwegian HF program suggested that trusting relationships can contribute to clients talking openly about substance use and/or mental health problems (Andvig et al, 2018). While our study involved a small sample which limits the conclusions that can be drawn, our data lends some support to the idea that substance use in HF programs tends to stabilize rather than increase or decrease.…”
Section: Discussionmentioning
confidence: 58%
“…Similary, both Baxter et al (2019) and Beaudoin (2016) found that HF resulted in no clear differences in substance use when compared with treatment as usual. Qualitative research from a Norwegian HF program suggested that trusting relationships can contribute to clients talking openly about substance use and/or mental health problems (Andvig et al, 2018). While our study involved a small sample which limits the conclusions that can be drawn, our data lends some support to the idea that substance use in HF programs tends to stabilize rather than increase or decrease.…”
Section: Discussionmentioning
confidence: 58%
“…In Norway, syringe distribution was introduced in the 1980s, OSPs since the 1990s, and in 2005, an injecting room opened in the capital, Oslo (Andvig et al, 2018). Recently, the government decided to establish a heroin substitution project (Norwegian Government, 2020).…”
Section: The Norwegian Contextmentioning
confidence: 99%
“…An example of harm reduction as a social practice is Housing First programming, where abstinence from drug use is not a condition for the provision of housing (Gaetz, Scott, & Gulliver, ), and where service providers invite PWUD to talk about their own understanding of their circumstances. Service providers also help the person attain financial stability and ensure access to entitled services (Andvig, Sælør, & Ogundipe, ). Conceptualizing harm reduction as a social practice also means the necessary engagement of PWUD in the design and implementation of interventions with the goal of ensuring relevance and acceptability (Harris).…”
Section: Harm Reduction As a Technical Solution Versus A Social Practicementioning
confidence: 99%